Atrial fibrillation risk in metabolically healthy obesity: A nationwide population-based study. (1st August 2017) - Lee, HyunJung; Choi, Eue-Keun; Lee, Seung-Hwan; Han, Kyung-Do; Rhee, Tae-Min; Park, Chan-Soon; Lee, So-Ryoung; Choe, Won-Seok; Lim, Woo-Hyun; Kang, Si-Hyuck; Cha, Myung-Jin; Oh, Seil
Abstract: Background: Metabolically healthy obese (MHO) individuals are reported to have a marginal increase in cardiovascular risk; however, their atrial fibrillation (AF) risk is unclear. We aimed to assess AF risk in MHO individuals and identify whether AF development is associated with obesity or influenced by metabolic comorbidities. Methods: A retrospective cohort of 389, 321 individuals (age, 45.6 ± 14.5 years; male, 52.1%) was extracted from the Korean National Health Insurance sample database between 2004 and 2006 and followed-up for new-onset AF until 2013. Subjects with diabetes mellitus, hypertension, and/or dyslipidemia were classified as "metabolically unhealthy." The cohort was stratified into four groups according to obesity and metabolic healthiness: metabolically healthy non-obese (MHNO), metabolically unhealthy non-obese (MUNO), MHO, and metabolically unhealthy obese (MUO). Results: AF was newly diagnosed in 5106 (1.3%) individuals during a mean follow-up of 7.5 ± 1.5 years. The AF incidence rates for the MHNO, MUNO, MHO, and MUO groups were 0.76, 2.66, 1.10, and 2.88 per 1000 person-years, respectively. Compared with the MHNO group, the MHO group had increased AF risk (adjusted hazard ratio, 1.30; 95% CI, 1.14–1.48) on multivariate analysis. One fourth of the MHO cohort became metabolically unhealthy, contributing to increased AF risk. Obesity was an independent risk factor for AF, and increased AF risk by 20%. Metabolic unhealthiness increased AF risk by around 40%, and of its components, hypertension contributed the most. Conclusions: MHO individuals are at increased risk for AF development, and obesity was independently associated with elevated AF risk.